Islamic Values Influence on Professional Ethical Commitment in Vocational Construction Education - Luthfi Luthfi; Lilis Marlina; Hilma Erliana; Intan Wulan Sari; Anni Alvionita Simanjuntak (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
The integration of Islamic values into vocational education remains a growing concern as efforts to balance technical competence with ethical integrity continue. This exploratory study examines how the understanding of Islamic values influences the professional ethical commitment of vocational education students in the construction sector. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the direct relationship between the two constructs. Data were collected from 39 purposively selected respondents with prior exposure to Islamic-based vocational ethics. The findings indicate that Islamic values have a positive and significant effect on ethical commitment (β = 0.520; p < 0.01), explaining 27% of the variance. The model's moderate explanatory power suggests that contextual and institutional factors beyond individual value comprehension also shape ethical commitment. Theoretically, this study contributes to the discourse on Islamic education by providing empirical evidence on integrating faith-based ethics into vocational pedagogy as a foundation for developing moral professionalism. Given the limited sample size and scope, the findings are exploratory and not broadly generalizable. Nonetheless, they underscore the practical importance of embedding Islamic values into vocational curricula to produce graduates who are not only technically proficient but also ethically consistent and socially responsible within the construction industry.